Maintaining protein stability of ∆Np63 via USP28 is required by squamous cancer cells. Issue 4 (4th March 2020) - Prieto‐Garcia, Cristian; Hartmann, Oliver; Reissland, Michaela; Braun, Fabian; Fischer, Thomas; Walz, Susanne; Schülein‐Völk, Christina; Eilers, Ursula; Ade, Carsten P; Calzado, Marco A; Orian, Amir; Maric, Hans M; et al.
Abstract: The transcription factor ∆Np63 is a master regulator of epithelial cell identity and essential for the survival of squamous cell carcinoma (SCC) of lung, head and neck, oesophagus, cervix and skin. Here, we report that the deubiquitylase USP28 stabilizes ∆Np63 and maintains elevated ∆NP63 levels in SCC by counteracting its proteasome‐mediated degradation. Impaired USP28 activity, either genetically or pharmacologically, abrogates the transcriptional identity and suppresses growth and survival of human SCC cells. CRISPR/Cas9‐engineered in vivo mouse models establish that endogenous USP28 is strictly required for both induction and maintenance of lung SCC. Our data strongly suggest that targeting ∆Np63 abundance via inhibition of USP28 is a promising strategy for the treatment of SCC tumours. Synopsis: The study reveals that squamous tumours are dependent on the expression of the deubiquitylase USP28. Inhibition of USP28 destabilises ΔNp63 protein abundance and enables therapeutic targeting of squamous tumours of various origins, such as head and neck, lung, cervix and pancreas. USP28 protein was upregulated in squamous tumours. USP28 modulated the expression of essential squamous genes by regulating ΔNp63 protein abundance. Pharmacologic inhibition of USP28 activity was well tolerated in vivo and negatively affected squamous tumour growth. Abstract : The study reveals that squamous tumours are dependent on the expression of the deubiquitylase USP28. Inhibition of USP28 destabilises ΔNp63 protein abundance and enables therapeutic targeting of squamous tumours of various origins, such as head and neck, lung, cervix and pancreas.